2016
DOI: 10.48550/arxiv.1609.05851
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Three-Point Vortex Dynamics as a Lie-Poisson System

Antonio Hernández-Garduño

Abstract: This paper studies the reduced dynamics of the three-vortex problem from the point of view of Lie-Poisson reduction on the dual of the Lie algebra of U (2). The algebraic study leading to this point of view has been given by Borisov and Lebedev [2, 3] (see also [4]). The main contribution of this paper is to properly describe the dynamics as a Lie-Poisson reduced system on (u(2) * , { , } LP ), giving a systematic construction of a one-parameter family of covectors {σ 1 , σ 2 , σ 3 } closely related to Pauli s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…, N − 1} such that n 1 + n 2 = N − 1, depending on the signs of the circulations {Γ j } N j=1 . More recently, Hernández-Garduño [12] (see also Hernández-Garduño and Shashikanth [13]) showed that the reduced dynamics of three point vortices may be written as a Lie-Poisson equation on u(2) * with the standard Lie-Poisson bracket by constructing a set of covectors satisfying the Pauli commutation relations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…, N − 1} such that n 1 + n 2 = N − 1, depending on the signs of the circulations {Γ j } N j=1 . More recently, Hernández-Garduño [12] (see also Hernández-Garduño and Shashikanth [13]) showed that the reduced dynamics of three point vortices may be written as a Lie-Poisson equation on u(2) * with the standard Lie-Poisson bracket by constructing a set of covectors satisfying the Pauli commutation relations.…”
Section: Resultsmentioning
confidence: 99%
“…as in (12). Notice that z is in C N−2 as opposed to C N−1 here; compare with (12). Then z provides a set of coordinates for the reduced space I −1 (0)/C.…”
Section: Proposition 23 (Reduction By Translational Symmetry)mentioning
confidence: 98%
See 1 more Smart Citation
“…This is shown using the Poisson structure of the three-vortex problem expressed in terms of symmetry invariants. A further account of this point of view is found in [17].…”
Section: Reduction By Rotational Symmetrymentioning
confidence: 94%
“…It follows that, in coordinates (r, s) ∈ C 2 , the matrix representation of the Hermitian metric restricted to P 0 is A B . Moreover, from (17),…”
mentioning
confidence: 97%